Implementasi h-CFTM (hybrid-Child Friendly Teaching Model) sebagai Penguat Merdeka Belajar Siswa SMP N 14 Semarang - Senowarsito, Senowarsito; Nugrahani, Dyah; Herlambang, Bambang Agus; Musarokah, Siti; Werdiningsih, Yuli Kurniati; Yulianti, Fitri (Journal of Dedicators Community, 2025)
This article with the title The Implementation of h-CFTM (hybrid-Child Friendly Teaching Model) as a Reinforcement for Independent Learning for Students at SMP Negeri 14 Semarang is the outcomes of Program Kemitraan Masyarakat (PKM) for SMP Negeri 14 Semarang in applying of h-CFTM (Hybrid-Child Friendly Teaching Model) as Strengthening Implementation Independent Student Learning. Partner in this PKM activity was SMP Negeri 14 Semarang, which is one of the Child Friendly Schools in Semarang City. The purpose of this writing is to clarify the outcomes of PKM, particularly those related to the implementation of h-CFTM at SMP Negeri 14 Semarang. PKM implementation methods included socialization, training, science and technology transfer, mentoring, monitoring, evaluation, and sustainability (follow-up). The common perception and commitment of the entire academic community in partner school, the implementation of the h-CFTM, as well as h-CFTM-Based Learning Management System are the outcomes of PKM (Hybrid-Child Friendly Teaching Model).